QUALITY OF HEALTH TECHNOLOGY ASSESSMENT REPORTS PREPARED FOR THE MEDICAL SERVICES ADVISORY COMMITTEE. (3rd October 2016) - Hua, Martin; Boonstra, Tristan; Kelly, Patrick J.; Wilson, Andrew; Craig, Jonathan C.; Webster, Angela C.
Abstract : Objectives: The Medical Services Advisory Committee (MSAC) makes recommendations to the Australian Government for funding health technologies under the Medicare Benefits Schedule (MBS). Differences in public, clinical, commercial, and political opinions on health expenditure emphasize the importance of defensible funding decisions. We aimed to evaluate the quality of health technology assessment (HTA) reports over time and among health technologies assessed for MSAC. Main Outcome Measures: A cohort study was performed of HTA reports prepared for MSAC between 1998 and 2013. We measured the quality of HTA reports using reporting guidelines proposed by the European Collaboration for Assessment of Health Interventions. Individual component scores across eleven domains were calculated, and summed for an overall aggregate score. We used linear regression to investigate any change in quality over time and among the types of technologies assessed. Results: We included 110 HTA reports. The safety (80 percent), effectiveness (84 percent), economic (74 percent), and organizational (99 percent) domains were better reported than the psychological, social, and ethical considerations (34 percent). The basic (75 percent), methodological (62 percent), background (82 percent), contextual (46 percent), status quo (54 percent), and technical information (66 percent) that framed each assessment were inconsistently reported. On average, overall quality scores increased by 2 percent ( p < 0.001) per year, from approximately 60 percent to 80 percent over the 15-year period, with no significant difference among surgical, diagnostic or other nonpharmaceutical health technologies ( p = 0.22). Conclusions: HTA reports prepared for MSAC are a key tool in allocating scarce health resources. The overall quality of these reports has improved, but the reporting of specific domains and subthemes therein could be better addressed.